From mandated coordination to public value: a systematic review of collaborative government management - Slamet Suwanto; Ednawan Prihana (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Indonesia's decentralized government relies on collaboration across ministries, regional agencies, villages, public-service units, businesses, universities, civil-society organizations, and communities. This review analyzes how such coordination is converted into integrated policy, joint implementation, and public value. A PRISMA-aligned search of indexed journal literature published in 2020-2025 identified 74 records; 35 articles remained after duplicate removal, screening, full-text assessment, and index verification. The corpus comprised 26 qualitative case/process studies, four mixed or quantitative studies, and five review, policy, or conceptual articles. Because designs and outcomes were heterogeneous, the study used structured extraction, design-sensitive methodological appraisal, and hybrid deductive-inductive thematic synthesis rather than statistical pooling. The synthesis indicates that collaboration is warranted when authority, knowledge, implementation capacity, and legitimacy are distributed across organizations; hierarchy remains necessary for legal authority, minimum standards, rapid command, and accountability. Five conditions repeatedly distinguish substantive collaboration from ceremonial participation: an authoritative mandate linked to resources, facilitative and boundary-spanning leadership, explicit roles and decision rights, integration of plans-budgets-data-workflows, and accountability for citizen outcomes. The proposed Indonesian Collaborative Government Management Cycle connects problem interdependence, actor architecture, shared intelligence, policy integration, joint delivery, and public-value learning. Its theoretical contribution is to position policy integration as the conversion mechanism between collaborative process and service outcomes, while treating mandated participation, decentralization capacity, power asymmetry, cultural legitimacy, and digital interoperability as contextual conditions.